2007
DOI: 10.2478/v10019-007-0013-x
|View full text |Cite
|
Sign up to set email alerts
|

Case report from Mayo Clinic: Locally advanced Bartholin gland carcinoma

Abstract: Case report from Mayo Clinic: Locally advanced Bartholin gland carcinoma Tumors of the Bartholin gland are rare, comprising less than 5% of all vulvar malignancies. Treatment is largely based on that of vulvar and anal squamous cell carcinomas. A case of invasive, grade 4, poorly differentiated squamous cell carcinoma of the Bartholin gland is presented. Our patient, a 47-year-old woman, had a history significant for cervical intraepithelial neoplasia treated with conization, type 2 diabetes mellitus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…One study of 33 patients reported a significantly higher incidence amongst African Americans; but did not identify any association with smoking status or BMI ( 2 ). Whilst some suggest BGC may be a sequelae of previous infection, in the majority of cases there is no pre-existing history of Bartholin gland disorders ( 9 , 10 ). The squamous cell subtype has, however, been linked to Human Papilloma Virus (HPV) ( 10 - 12 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…One study of 33 patients reported a significantly higher incidence amongst African Americans; but did not identify any association with smoking status or BMI ( 2 ). Whilst some suggest BGC may be a sequelae of previous infection, in the majority of cases there is no pre-existing history of Bartholin gland disorders ( 9 , 10 ). The squamous cell subtype has, however, been linked to Human Papilloma Virus (HPV) ( 10 - 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…Whilst some suggest BGC may be a sequelae of previous infection, in the majority of cases there is no pre-existing history of Bartholin gland disorders ( 9 , 10 ). The squamous cell subtype has, however, been linked to Human Papilloma Virus (HPV) ( 10 - 12 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations